Interaction of Music as a Soft Power in the Dimension of Cultural Diplomacy between Indonesia and Thailand - Surasak Jamnongsarn (IJCAS (International Journal of Creative and Arts Studies), 2014)
The phenomenon of cultural diplomacy between Indonesia and Thailand had appeared since the visit of the Kings of Thailand to Java more than a hundred years ago. In addition, the Indonesian immigrants who has come to Thailand are also an important factor of musical history of both countries. As a result of these interactions, the exchange of ideas, information, value, system, tradition, belief, and other aspects of culture are in the interest of foster mutual understanding through musical dimension. More precisely, the interaction contributes to the exchange of musical ideas. In the Thai music history, angklung and gamelan is an essential tool for building international relations between the two countries at the community level. The relation between the two countries is similar to the relationship between two people so that emotion is the key methodologies in cultural diplomacy. The purpose of diplomacy is to give those people around you to know you better. There used to be a lot of cultural imperialism in cultural diplomacy, but this should be avoided. Currently, cultural diplomacy can give an idea on how a country engaging with others, a capacity to share and accept other viewpoints. The music has a very positive impact for the development of musical culture in Thailand today.Angklung has been taught in every elementary school in the whole of Thailand, even at the level of junior high school and high school. The ideas of new works by Thailand composers today inspired many of the gamelan orchestra. Despite the fact may be felt by the people of Thailand that the influence of Indonesian music is so powerful, so far no Thai person who writes about the history of this music as cultural diplomacy. Cultural diplomacy conceived and built in three models of representation: soft power, nation branding, and cosmopolitan constructivism.